Groundwater age, brine migration, and large‐scale solute transport in the Alberta Basin, Canada. Issue 4 (6th March 2015) - Gupta, I.; Wilson, A. M.; Rostron, B. J.
Abstract: There is a great contrast in geochemical and hydrogeologic estimates of the residence times of pore fluids in sedimentary basins. This contrast is particularly evident in the Alberta Basin, Canada, which has served as the study area for important studies of long‐term fluid flow and transport. To address these differences, we developed two‐dimensional simulations of groundwater age, constrained by both hydrogeologic and geochemical observations, to estimate the residence time of fluids and the amount and timing of flushing by meteoric waters in the Alberta Basin. Results suggest that old, residual brines have been retained in the deepest parts of the basin since their formation ca. 400 Ma, but significant dilution by younger waters has reduced the age of these pore waters to no more than approximately 200 My. Shallower formations have been flushed extensively by fresh, young waters. Loss of brines and dilution of older pore waters occurred primarily after the uplift of the Rockies with the introduction of the gravity‐driven flow regime. Despite these large changes in flow regime, solute exchange between deep saline aquifers and the overlying vigorous freshwater flow system was found to be consistent with long‐term dispersive mixing across subhorizontal concentration gradients rather than by direct flushing. Sensitivity studies using an analytic solution supported the use of 100 m for transverse dispersivity in large‐scale numerical models. These simulations confirm that the age and origin of brines are in many cases poor indicators of long‐term solute transport rates in sedimentary basins, but the geochemical indicators that are used to determine the origin of brines can provide useful constraints for calculating groundwater age and are far more commonly available than isotopic groundwater age tracers.